Influência da sanitização e do armazenamento nos compostos bioativos de manga 'palmer' in natura e processada - Monaco, Kamila de Almeida [UNESP] (2015)
The aim of this study was to investigate the influence of sanitizers (ozone and sodium hypochlorite) in the bioactive compounds content and antioxidant activity during cold storage and marketing simulation grown in mango (Mangifera indica L.) grown in organic and conventional system and verify changes during storage of two different smoothies. To achieve this thesis objective was divided into five sections, the first the mango 'Palmer' organic acquired in Borborema-SP and conventional, donated by Ogata Citrus (Taquaritinga-SP) were transported to the laboratory of Biochemistry, which were submitted four immersion treatments: immersion in water; in chlorinated water with 100 mg L-1 of sodium hypochlorite for 10 minutes and ozonated water for 10 and 20 minutes. The evaluations were performed after harvest and at 7 and 15 days of cold storage. At 7 days, fruit were taken to the environment and evaluations followed by 4 and 8 days, to simulate marketing period. Were determined firmness, pH, ascorbic acid, soluble solids, titratable acidity, total polyphenols, total flavonoids, β-carotene, DPPH and FRAP. The microbiological analyzes were carried out after harvest, after 7 days of cold storage and 7 days over 4 environment. The design was completely randomized (CRD) with factorial 5 x 8 (day trial x treatments) with three repetitions. There was a trend of organic fruit and ozonated have higher bioactive compounds contents, therefore higher antioxidant activity, which shows that ozone could replace chlorine without damage to fruit. In the second chapter, it performed the bioactive amines quantification of the pulp mango 'Palmer' organic and conventional, undergo four sanitization treatments: immersion in the tap water; in chlorinated water with 100 mg L-1 of sodium hypochlorite for 10 minutes and ozonization for 10 and 20 minutes postharvest and after seven days of cold storage followed by 4 and 8 ...